Injury patterns of professional footballers in the Spanish first division during the 2017-2018 seasons - Prieto-Lage, I.; Louzao-Neira, I.; Argibay-González, J. C.; Gutiérrez-Santiago, A. (Physiology & Behavior, 2020)
The objective of this research is to detect and analyze the injury patterns that were produced during the 2017-2018 seasons in the Spanish league. The study of the injuries in football concerns the scientific community and the clubs, due to the economic losses and the sports that are involved. The sample comprised 116 detected injuries through the database of TransferMarkt. The analysis incorporates official medical reports of the clubs. In order to obtain the results, we used different analysis techniques: statistical analysis with SPSS, the detection of T-Patterns with Theme and the analysis of polar coordinates with HOISAN. The most common injury was muscle strain (49.6%), where the hamstring fibrillary rupture protrudes, followed by sprains (17.1%) and bruises (16.3%). Generally, the players injured themselves (61.8%) and in the defensive zone (59.3%). There was a change in the trend regarding the player that injured themselves the most; formerly, the midfielder, and currently, the defender. It appears that a week-long rest is not effective, because the players injure themselves in the first 200 min after that rotation. Strains occur more frequently when the players are competing for more than 1,000 h, especially the ones in the defense and forward positions.